A distinction of cow and buffalo ghee using principal component analysis of triglyceride composition. (17th February 2021) - Pathania, Parul; Sharma, Vivek; Rao, Priyanka Singh; Arora, Sumit; Panjagari, Narender Raju
Abstract : Triglyceride (TG) profiling was explored to distinguish cow ghee from buffalo ghee to check their admixing. Cow and buffalo butter was clarified at 110, 130 and 150 °C to obtain ghee. Temperature of clarification did not show any significant effect on TG profile. Cow ghee showed maxima at TG C38 and C52. Buffalo ghee exhibited maxima at C38 and C50 unlike cow ghee. Cow ghee samples showed a higher TG content of C42 to C54, whereas buffalo ghee samples were associated with a greater content of C26 to C38. Principal component analysis (PCA) and hierarchical clustering showed two ghee types as distinct separate clusters. Abstract : Triglyceride Profiling of cow and buffalo ghee.